« Mostaganem avant l’envahissement » : fragments de discours numériques autour de l’appropriation de l’espace de la ville - Ibtissem Chachou (Les Cahiers d’EMAM)
In this article, I spot the light on a discourse extracted from a digital corpus from a Facebook page entitled Mostaganem of the 50s. This latter has been posting/distributing old photographes of the city since 2012. The page has around 16 600 suscribers. The comments that goes with those “posts” often lead the internet users to an exchange and debats about the posted pictures (street, quarter, bridge, villa, gardin, hospital, market etc.) and leave tensions between the city’s inhabitants. In fact, the analysis of the statements that constitue our corpus shows that malaises socio-urban feed and strengthen the “traditional” intra-urbans fractures among those “townsfolk” “Old” and “natives/real inhabitants” of the city and those who come recently. Those malaises have problems related to the population density, urban protection, incompetent electers, safeguarding and restoration of material heritage, urbanisation of the city, etc.